English Teachers' Perception and Strategies Towards the Use of Code-Switching in Teaching EFL Young Learners - Putu Andre Sastra Sastra; Kadek Yunita Adriyanti (Universitas Muhammadiyah Kalimantan Timur, 2022)
The study was aimed to investigate the English teachers’ perception of the effectiveness of using code-switching to the EFL young learner at SD Lab Undiksha Singaraja, Bali and to find out the strategy used by the teachers in using code-switching to teach the EFL young learners. The study used mixed method design with 5 English teachers of SD Lab Undiksha as the participant. A questionnaire with a total of 18 items was distributed and an interview was conducted to collect the data related to the teachers’ perception, which covered the teachers’ perception related to the teachers’ persona, subject access, classroom management, and interpersonal relations. Then, to answer the second research question related to the strategy of code-switching used by the teachers, an interview was conducted. The result showed that there were 50% teachers had positive perception in relation to teachers’ persona, 70% teachers had positive perception in relation to subject access, 84% teachers had positive perception in relation to classroom management, and 80% teachers had positive perception in relation to interpersonal relations. Relating to the strategy, the results revealed that the teachers usually did code-switching whenever they introduced or say English vocabulary that were considered new or difficult for the students. It was done by either inserting the English or Bahasa Indonesia words in between their utterance. This indicated that the perception towards code-switching in teaching English was perceived positively and was implemented in order to ease the students in understanding the target language.